Functional Antibody Responses Following Allogeneic Stem Cell Transplantation for TP53 Mutant pre-B-ALL in a Patient With X-Linked Agammaglobulinemia - van Zelm, Menno C.; Pumar, Marsus; Shuttleworth, Peter; Aui, Pei M.; Smart, Joanne M.; Grigg, Andrew; Bosco, Julian J. (Frontiers in Immunology, 2019)
Patients with X-linked agammaglobulinemia (XLA) have failure of B-cell development with lack of immunoglobulin (Ig) production. While immunoglobulin replacement therapy (IgRT) is beneficial, XLA patients remain at risk for infections, structural lung damage, and rarely, neoplasia. Allogeneic stem cell transplantation (alloSCT) may offer a potential cure, but is associated with significant life-threatening complications. Here, we present a 25-year old XLA patient who developed pre-B acute lymphocytic leukaemia (ALL) with somatic TP53 mutation, and treatment for this high-risk malignancy involved full myeloablative conditioning and a HLA-matched sibling alloSCT. Full donor chimerism was achieved for CD3+ and CD3- cell fractions. The patient remains in morphological and flow cytometric remission 14 months post-transplant, with late-onset oral GvHD requiring low dose prednisolone and cyclosporin. Following IgRT discontinuation at 4 months post-transplantation, humoral immunity was established within 14 months as reflected by normal numbers of total B cells, memory B cells, serum IgG, IgM and IgA, and production of specific IgG responses to Prevenar-13 vaccination. This is only the second reported case of an XLA patient with pre-B-ALL, and the most detailed report of engraftment following alloSCT in XLA. Together with the two previous XLA cases treated with alloSCT, our report provides evidence for the potential for successful humoral reconstitution with alloSCT in patients with B-cell intrinsic antibody deficiency. These observations may be relevant given IgRT, while beneficial, remains an imperfect solution to long-term infectious complications.